The Role of Financial Controlling in the Management System of Tourism and Recreational Company (Laisvalaikio tyrimai, 2018)
In the modern world tourism and recreation are highly profitable activities, which also have a significant impact on the economy of the country, contributing to the inflow of foreign currency, creating new jobs, improving infrastructure and so on. In the conditions of economic instability and high level of market competition, success of financial-economic activity of tourist enterprises is determined by the efficiency of decision-making that directly depends on the total access to information about the financial state and existing risks. The aim of the research was to identify the role of financial controlling in the management system of tourist-and-recreational company. Research methods used for this research paper were analysis, synthesis, comparison, classification and grouping of functions and objectives of the object being studied. The object was the role of financial controlling in the management system. It is believed that controlling as economic term was discovered in Europe in the 15th century, after that it gained a wide development in the United States. In Russia, the concept of controlling became popular in the 1990s. Conclusions: 1. The main task of financial controlling is to maintain profitability and ensure liquidity, i.e. the ability of the enterprise to fulfil its payment obligations at any time that is most relevant for the tourism industry. Among the key challenges faced by resort companies, it is important to headline the seasonality of demand, which largely affects the using of their material resources. The duration of the active period can vary from 90 to 180 days; it often depends on climate and a number of other factors (Zlenko, 2015). In order to stabilize the work during the off-season, maintain financial stability and solvency in recent years many tourism and recreational enterprises began to strive for the introduction of modern management systems. 2. An effective system of financial controlling at a tourist and recreational enterprise allows fully assessing the current position of the company, making forecasts and successfully resisting external destabilizing factors.Keywords: financial controlling, control system, tourism and recreational company.